The Concept of Rights of Nature in Colombia and Ecuador: Lessons for a ‘Good Life’ in Urban Spaces - Marie-Christine Fuchs (Global Environment)
In Colombia and Ecuador, the concept of the rights of nature has found its way into both legislation and jurisprudence in recent years. It can be seen as the ‘juridification’ of the concept ‘buen vivir’ which transfers indigenous cosmovisions into law. This article reflects on the influence and possible transferability of the concept, which has been elaborated upon and concretised in ground-breaking judgements by the Colombian and Ecuadorian constitutional courts, to Europe. It poses the question of whether the rights of nature must be understood as material postulates or rather constitute ‘decorative elements’. This article also critically reflects on whether and how the concept of the rights of nature could be of benefit for a ‘good life’ in urban areas in the sense of, for example, a higher level of environmental and species protection, better living conditions for cities’ inhabitants or an increased cultural identification with the city.